Thermal conductance of nanosize semiconductor pillars. Issue 1 (1st November 2012) - Bartsch, Thorben; Wetzel, Alina; Sonnenberg, David; Schmidt, Matthias; Heyn, Christian; Hansen, Wolfgang
Abstract We study the thermal transport through only few nanometer long GaAs pillars. The pillars are epitaxially embedded between two otherwise isolated thermal reservoirs. Because of the short length and absence of defects and interfaces, the heat current through the pillars is free of distracting influences and perfectly controlled. This enables simple understanding of the observed thermal transport, regarding the pillars as ballistic thermal point contacts. The adjacent figure sketches a side view of the structures employed for the experiments. The thermal conductance of the pillars was measured with the 3ω method. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Scheme of the investigated heterostructure with heater and thermal anchor.